Wartości społeczne w "Monitorze" = Social values in "Monitor" - Jaros, Violetta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of this paper is an initial analysis and a brief description of the social values proposed by "Monitor". The values propagated by the royal party were to be the driving force of everyday actions taken by the citizens of the then Republic of Poland.
Keywords: "Monitor" - czasopismo; wartość; antywartość; wartości społeczne; oświecenie; values; antivalue; social values; Enlightenment